Developing a GeoGebra-Assisted Web-Based Learning Module for Analytical Geometry in a STEM Context - Hidayat, Dayat; Palupi, Evangelista L W; Susanah, Susanah; Setianingsih, Rini; Sancoko, Candra (Universitas Islam Negeri Sunan Kudus, 2024)
In modern education, incorporating technology is crucial for enhancing learning experiences and ensuring equal access to education. By integrating technology, educators can create interactive and immersive learning environments that boost student engagement and motivation. This research aims to describe the development process and results of a GeoGebra-assisted, web-based module for analytical geometry within a STEM context. The research follows the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. Data collection methods include questionnaires, documentation, and literature reviews. Feasibility validation assesses the module's face and content validity, focusing on content, language, and appearance. Data analysis utilizes a Likert scale to assess the validity of the module's aspect categories. The results indicate that the web-based module was developed in accordance with each stage of the ADDIE model. Expert feasibility tests show that the module demonstrates good validity in terms of content, language, and appearance. Dalam pendidikan modern, mengintegrasikan teknologi sangat penting untuk meningkatkan pengalaman belajar dan memastikan akses pendidikan yang merata. Dengan mengintegrasikan teknologi, pendidik dapat menciptakan lingkungan belajar yang interaktif dan imersif yang meningkatkan keterlibatan dan motivasi siswa. Penelitian ini bertujuan untuk mendeskripsikan proses dan hasil pengembangan modul berbasis website berbantuan geogebra untuk geometri analitik pada konteks STEM. Penelitian ini merupakan penelitian pengembangan menggunakan model ADDIE yang terdiri dari 5 tahap yaitu analisis, desain, development, implementation, dan evaluation. Teknik pengumpulan data menggunakan angket, dokumentasi, literatur review. Validasi kelayakan dilakukan untuk mengetahui validitas muka dan isi pada modul berbasis website ini yang meliputi validitas konten, bahasa, dan tampilan. Analisis data menggunakan skala likert untuk mengetahui kelayakan aspek kategori. Hasil penelitian menunjukkan bahwa modul berbasis website telah dihasilkan berdasarkan tahapan setiap proses model pengembangan ADDIE dan berdasarkan uji kelayakan oleh para ahli, validitas dari modul berbasis website ini adalah baik dalam hal konten, bahasa, dan penampilan.